Evaluation of the effect of the strain rate on the tensile properties of carbon–epoxy composite laminates. (September 2017) - Kwon, Junbeom; Choi, Jaeyoung; Huh, Hoon; Lee, Jungju
This paper is concerned with evaluation and prediction of the tensile properties of carbon fiber-reinforced plastics laminates considering the strain rate effect at intermediate strain rates. Uniaxial tensile tests of carbon fiber-reinforced plastics laminates were conducted at various strain rates ranging from 0.001 s –1 to 100 s –1 using Instron 8801 and a high speed material testing machine to measure the variation of the elastic modulus and the ultimate tensile strength. Tensile test specimens were designed based on the ASTM standards and stacked unidirectionally such as [0°], [90°] and [45°] to predict the elastic modulus of carbon fiber-reinforced plastics laminates with various stacking sequences. The axial strain was measured by the digital image correlation method using a high speed camera and ARAMIS software to enhance the accuracy of the strain measurement. A prediction model of the elastic modulus of carbon fiber-reinforced plastics laminates is newly proposed in consideration of the laminate theory and the tensile properties of unidirectional carbon fiber-reinforced plastics laminates. The prediction model was utilized to predict the tensile properties of [0°/90°]s laminates, [±45°]s laminates, and [0°/±45/90°]T laminates for validation of the model. The elastic moduli predicted were compared with the static and dynamic tensile test results to confirm the accuracy of the prediction model.